A gathering in Hope : a novel - Gulley, Philip (Hope, 2016)
"Bestselling author Philip Gulley offers humorous, small-town storytelling as he follows the foibles and follies of Pastor Sam Gardner. Thanks to an unexpected windfall, Sam Gardner's congregation (with the exception of a few malcontents) is eager to expand their meetinghouse. But before building can commence, the County Environmental Board and the Department of Natural Resources put the quietus on the plan. A colony of endangered Indiana bats have made the tree beside the meetinghouse, and the meetinghouse attic, their place of hanging, mating, and living, which poses a big problem for the congregation. Aside from the fact that their fanged visitors are engaging in sinful acts on church property, until these bats leave for hibernation, Hope Friends Meeting is left without a gathering place. And when an over-zealous Leonard Fink takes matters into his own hands, he may even land himself--and Sam--in jail"--